Studies on ion-pairing effects of the kinetics of aquation of bromopentaammine cobalt(III) complex in malonate media - Zeitouni, Farah Samih; El-Subruiti, Gehan Moustafa; Younes, Ghassan Omar; Amira, Mohammad Fawzi (European Journal of Chemistry, 2011)
The aquation of bromopentaamminecobalt(III) ion in the presence of ion-pairing malonate anion in mixed solvent media of water with tert-butanol (10%-50%) v/v have been investigated spectrophotometrically at different temperatures (30-60 oC). Nonlinear plots of Log (kip) ion-pair rate constants against the reciprocal of the dielectric constant D, Log of water concentration and Grunwald-Winstein Y values were found. The thermodynamic and extrathermodynamic analyses of the kinetic data have been discussed in terms of solvent effect on the ion-pair aquation reactions. The obtained isokinetic temperatures of these systems indicate the existence of compensation effect arising from solute-solvent interaction. The extrema found in the change of ∆Hip* and ∆Sip*with the mole fraction of the co-solvent can be attributed to the change of the physical properties of the solvent-water mixture with the solvent structure. Application of a free energy cycle is performed to compare between the stability of the initial and the transition state of the complex. However, small changes in ∆Gip*with the mole fraction of the co-solvent was found, indicating a compensating effects between ∆Hip* and ∆Sip*